Deployed research. Issue 2 (30th April 2014) - Nordmann, Giles; Woolley, T; Doughty, H; Dalle Lucca, J; Hutchings, S; Kirkman, E
Abstract : The Role 3 Medical Treatment Facility (Field Hospital) in Camp Bastion (R3 Bastion) is acknowledged to be one of the busiest dedicated trauma facilities in the world. Casualties typically present with severe injuries and in physiological extremis. These casualties form a unique cohort representing the most relevant population to evaluate the effectiveness of treating battlefield injuries as academic clinicians and scientists interested in trauma seek to improve outcomes for such patients in the future. This article describes four separate but related research projects that have been undertaken in Camp Bastion, Afghanistan, over the last year. They traverse the spectrum of clinical research, ranging from data collection to a randomised control trial. The aim is to discuss some of the problems encountered and the solutions that made it possible to undertake research in a theatre of operations, thereby providing a starting point for others who may wish to initiate research in a similar environment.